Thermodynamics fundamentals for applications - O'Connell, John P. (Cambridge University Press, 2005)
Thermodynamics: Fundamentals and Applications is a 2005 text for a first graduate course in Chemical Engineering. The focus is on macroscopic thermodynamics; discussions of modeling and molecular situations are integrated throughout. Underpinning this text is the knowledge that while thermodynamics describes natural phenomena, those descriptions are the products of creative, systematic minds. Nature unfolds without reference to human concepts of energy, entropy, or fugacity. Natural complexity can be organized and studied by thermodynamics methodology. The power of thermodynamics can be used to advantage if the fundamentals are understood. This text's emphasis is on fundamentals rather than modeling. Knowledge of the basics will enhance the ability to combine them with models when applying thermodynamics to practical situations. While the goal of an engineering education is to teach effective problem solving, this text never forgets the delight of discovery, the satisfaction of grasping intricate concepts, and the stimulation of the scholarly atmosphere